Complex Network Analysis of Pakistan Railways. (18th March 2014) - Mohmand, Yasir Tariq; Wang, Aihu
Abstract : We study the structural properties of Pakistan railway network (PRN), where railway stations are considered as nodes while edges are represented by trains directly linking two stations. The network displays small world properties and is assortative in nature. Based on betweenness and closeness centralities of the nodes, the most important cities are identified with respect to connectivity as this could help in identifying the potential congestion points in the network.